Environment and agriculture of early Winchester - Biddle, Martin,; Renfrew, Jane M.,; Ottaway, Patrick, (Winchester studies ;, 2022)
This wide-ranging study describes the natural environment of Winchester and its immediate surroundings from the late Iron Age to the early post-medieval period. Historical and archaeological evidence consider humanity's interactions with the environment, fashioning agricultural, gardening and horticultural regimes over a millennium and a half.